Women from Traditional Islamic Educational Institutions in Indonesia Negotiating Public Spaces - Srimulyani, Eka (IIAS Publications Series, 2012)
In this insightful book, Eka Srimulyani provides a new look at the role of women in Islamic educational institutions in Indonesia. Women at these traditional schools, called pesantren, play a significant role in the shaping of gender relations in the Indonesian Muslim community, and have not, until recently, garnered as much attention in the academic community as they undoubtedly deserve. This deeply informative study offers a new perspective on why Muslim feminism has found a powerful foothold in Indonesia, and it creates a vivid portrait of the lives of pesantren.